2015
DOI: 10.1016/j.meegid.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

A selective sweep in a Varroa destructor resistant honeybee (Apis mellifera) population

Abstract: The mite Varroa destructor is one of the most dangerous parasites of the Western honeybee (Apis mellifera) causing enormous colony losses worldwide. Various chemical treatments for the control of the Varroa mite are currently in use, which, however, lead to residues in bee products and often to resistance in mites. This facilitated the exploration of alternative treatment methods and breeding for mite resistant honeybees has been in focus for breeders in many parts of the world with variable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 50 publications
(51 reference statements)
3
23
0
2
Order By: Relevance
“…They found a strong overall loss of heterozygosity in these regions, suggesting that genetic drift, selection, or both had occurred in the population. On two loci on chromosome 7, the reduction was greater than what could be expected from genetic drift alone (Lattorff et al 2015). suggesting that this small genomic region experienced strong selection (Lattorff et al 2015).…”
Section: Gotland Swedenmentioning
confidence: 82%
See 2 more Smart Citations
“…They found a strong overall loss of heterozygosity in these regions, suggesting that genetic drift, selection, or both had occurred in the population. On two loci on chromosome 7, the reduction was greater than what could be expected from genetic drift alone (Lattorff et al 2015). suggesting that this small genomic region experienced strong selection (Lattorff et al 2015).…”
Section: Gotland Swedenmentioning
confidence: 82%
“…On two loci on chromosome 7, the reduction was greater than what could be expected from genetic drift alone (Lattorff et al 2015). suggesting that this small genomic region experienced strong selection (Lattorff et al 2015). A promising candidate gene identified in this genomic region of the honeybee that may be significant in affecting the mite's reproduction was a glucosemethanol-choline oxidoreductase (GMCOX18).…”
Section: Gotland Swedenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there 75 are some feral honey bee populations that have been able to rapidly acquire tolerance to Varroa, often in just a couple of years after an initial period of high mortality (Pinto et al 2004;Loper et al 2006;Villa et al 2008;Mikheyev et al 2015). Studies of genome-wide historical changes in such populations can allow us to understand the mechanisms of resistance to Varroa as well as how selection for disease resistance occurs in natural populations (Behrens 80 et al 2011;Lattorff et al 2015;Mikheyev et al 2015).…”
Section: Introduction 45mentioning
confidence: 99%
“…Hudson et al[30,31], e.g., detected a ~50-kb selective sweep surrounding the SOD locus in Drosophila melanogaster. Using high-density QTL markers, Lattorff et al[32] detected a locus in the honeybee Apis mellifera where the allele frequency reached near fixation (allele frequency = 0.97) in a period of seven years under selection with the ectoparasitic mite Varroa destructor. Within the context of pesticide selection, only a handful of studies have identified sweeps associated with resistance and, in all cases to date, the sweeps were relatively small (< 200 kb).…”
mentioning
confidence: 99%